Preparation method of carbon-based nano LiFePO4 composite positive electrode material
By using biomass carbon source and molten salt medium to prepare self-assembly of porous carbon-based and nano LiFePO4 at high temperature, the low specific capacity and high reaction temperature of LiFePO4 batteries are solved, the charging and discharging performance and production cost of the batteries are improved, and the charging and discharging performance and production cost of the batteries are achieved. High-performance carbon-nano-LiFePO4 composite cathode material suitable for industrial production.
Patent Information
- Application Number
- CN202411459445.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-03
AI Technical Summary
Due to its low theoretical specific capacity and insufficient electronic conductivity, the existing LiFePO4 batteries have limited their application under fast charging conditions, and the preparation process is complex and costly, making it difficult to meet the needs of high-energy-density fast charging batteries.
Walnut shells, ginkgo leaves and bamboo powder biomass are used as carbon sources. After carbonization in a tube furnace, NaCl-KCl molten salt medium and pore-forming agent are combined to prepare porous carbon-based materials by melt-melting salt method, and at high temperatures React with raw materials such as NH4H2PO4, FeC2O4·2H2O, CH3COOLi, etc., realize self-assembly of porous carbon-based and nano LiFePO4, reduce the reaction temperature and sintering cycle, and improve the electronic conductivity and ion diffusion rate of the material.
Successfully improve the voltage platform, battery capacity and charge and discharge rate of LiFePO4 batteries, reduce production costs, achieve better Li+ and electronic transmission performance, is suitable for industrial production, and broaden the high-performance carbon matrix/nano-LiFePO4 composite cathode material Production path.
Smart Images

Figure CN119240647A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium iron phosphate positive electrode materials, and in particular to a method for preparing a carbon-based-nano LiFePO4 composite positive electrode material. Background Art
[0002] At present, there is an obvious "structural overcapacity" in the lithium battery material market, that is, there is an overcapacity of low-end positive and negative electrode materials, but there is a shortage of high-end positive and negative electrode materials. With the increasing requirements of lithium-ion batteries for energy density and fast charging performance, the positive electrode materials of lithium-ion batteries are required to have high energy density while also improving the fast charging performance of the materials. At present, the main commercial positive electrode materials are LiFePO4 and ternary lithium-ion batteries (NCM). Among them, LiFePO4 batteries are widely used in transportation, aerospace, defense industry and medical health fields due to their extremely long cycle life (5000 times), excellent safety performance, environmental protection and rich raw material reserves. However, LiFePO4 batteries have a theoretical specific capacity of 170mAh / g, low electronic conductivity and one-dimensional lithium ion diffusion characteristics, resulting in low rate capacity, which limits their further application under fast charging conditions and gradually makes it difficult to meet the needs of high energy density fast charging batteries. In order to improve the capacity and fast charging performance of LiFePO4 materials, surface modification, element doping, and particle nano-sizing are generally used. However, this has limited improvement on LiFePO4 batteries, and it is still difficult to break through the theoretical specific capacity of 170mAh / g and the low charging rate problem. Therefore, it is necessary to break the conventional way and modify the LiFePO4 material in the form of a composite positive electrode material to increase the capacity of LiFePO4 batteries, increase the diffusion rate of ions during charging and discharging, reduce electronic impedance, and improve rate performance.
[0003] For example, Chinese patent application No. 202011353869.6 discloses a method of first preparing nano-LiFePO4 by a solvent method, and then preparing LiFePO4@C material using citric acid and ethylene glycol as carbon sources. The research results show that: LiFePO4@C composite materials can effectively improve the transmission rate and diffusion coefficient of lithium ions in LiFePO4, and carbon conductive materials can effectively improve the electronic conductivity of materials; the amorphous carbon of citric acid and ethylene glycol synergistically exhibits good lithium ion conductivity and electronic conductivity, effectively improving the performance, safety and cycle performance of LiFePO4 materials. However, the LiFePO4@C material prepared by this method has the defects of no obvious performance improvement, complex process flow, and poor contact between LiFePO4 and C interface when using non-in-situ preparation.
[0004] Therefore, the research on carbon-based-nano LiFePO4 composite cathode materials based on amorphous carbon structure is still worth exploring. It is necessary to study the role of amorphous carbon matrix in nano-LiFePO4 to improve the LiFePO4 battery Li + One-dimensional diffusion characteristics, improve the voltage platform, battery capacity and LiFePO4 + and electron transfer rate, improve the fast charging performance of LiFePO4 batteries, explore a production path suitable for industrial production and expand the market for high-performance carbon matrix / nano-LiFePO4 composite positive electrode materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a carbon-based-nano LiFePO4 composite positive electrode material, which solves the problems of high production cost, high reaction temperature, long sintering cycle, and limited capacity and rate performance in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a carbon-based-nano LiFePO4 composite positive electrode material, comprising the following steps:
[0007] (1) Using walnut shells, ginkgo leaves, and bamboo powder as raw materials, carbonizing them at 300°C-600°C for 0.5h-3h in a tubular furnace under an inert atmosphere, and removing volatile substances to obtain a biomass carbon source; then using NaCl-KCl (molar ratio of 1:1) as a molten salt medium, Na2CO3, K2CO3, and KOH as pore-forming agents, and the mass ratio of pore-forming agent to reactant is 0.3-3, in a tubular furnace under an inert atmosphere, at 800°C-1300°C to prepare a porous carbon-based material;
[0008] (2) NaCl-KCl (molar ratio of 1:1) was selected as the molten salt medium, and NH4H2PO4, FeC2O4·2H2O, CH3COOLi, C6H 12 O6 is used as a raw material, and the porous carbon-based material prepared by the present invention or commercial graphene is added. The molar ratio of the molten salt / reactant raw material is prepared in the range of 0.3:1-3:1, and a multi-molecular carbon source is used as a binder. The reactant raw materials are weighed in proportion, mixed and loaded into a crucible, and placed in a tubular furnace for heating. An inert atmosphere is introduced, and when the temperature rises to 600°C-900°C, self-assembly of the porous carbon-based material and carbon nano-LiFePO4 is achieved in the molten salt. The temperature is maintained for a range of 0.2h-8h and then reduced, and the powder is cooled to room temperature with the furnace, washed with hot water, filtered to separate the molten salt, and dried to prepare a powder, which is a carbon-based-nano LiFePO4 composite positive electrode material.
[0009] Compared with the prior art, the present invention has the following beneficial effects:
[0010] (1) Using walnut shells, ginkgo leaves, and bamboo powder carbon materials as raw materials can greatly reduce the production cost of carbon-based-nano LiFePO4 composite positive electrode materials, and using biomass as a carbon source is in line with the current development trend of lithium-ion batteries.
[0011] (2) Using molten salt as the medium can reduce the reaction temperature and realize the preparation of particle-reinforced composite materials in a short process and with controllable particle size. Molten salt can promote mass transfer of reactants, and the reactants are well mixed, which can greatly reduce the reaction temperature. The particle size distribution of particle-reinforced composite powders can be controlled by regulating kinetic factors. This can solve the problems of high reaction temperature, long sintering cycle and difficult to control particle size in the current preparation process of LiFePO4.
[0012] (3) Adding multi-molecular carbon sources as binders to achieve self-assembly of porous carbon-based materials and nano-LiFePO4 in molten salts, nano-LiFePO4 can be dispersed on the two-dimensional carbon-based materials, and the agglomeration of nano-LiFePO4 is eliminated as much as possible. The self-assembly structure of carbon-based materials and nano-LiFePO4 enables nano-LiFePO4 to be dispersed in the two-dimensional carbon-based materials, which can give full play to the advantages of high electronic conductivity of carbon materials, improve the voltage platform, battery capacity and Li of LiFePO4 + and electron transfer rate to improve LiFePO4 battery Li + One-dimensional diffusion characteristics, and a carbon-based-nano LiFePO4 composite positive electrode material with good interface contact state can be obtained on an in-situ basis. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 The C6H prepared by the present invention 12 Macroscopic image of O6 carbon-based-nano LiFePO4 composite material;
[0014] Figure 2 The C6H prepared by the present invention 12 XRD patterns of O6 carbon-based and pure nano-LiFePO4;
[0015] Figure 3 The C6H prepared by the present invention 12 XRD pattern of O6 carbon-based-nano LiFePO4 composite material in the range of 2θ 20°-40°;
[0016] Figure 4 This is a scanning electron microscope image of the porous bamboo powder carbon matrix prepared by the present invention;
[0017] Figure 5 The C6H prepared by the present invention 12 SEM image of O6 carbon base;
[0018] Figure 6 The C6H prepared by the present invention12 Scanning electron microscope image of O6 carbon-based-nano LiFePO4 composite material;
[0019] Figure 7 The C6H prepared by the present invention 12 The charge and discharge curve of O6 carbon-based-nano LiFePO4 composite material at 0.1C;
[0020] Figure 8 The C6H prepared by the present invention 12 dQ / dV curve of O6 carbon-based-nano LiFePO4 composite material at 0.1C;
[0021] Fig. 9 The C6H prepared by the present invention 12 Specific capacity-voltage curve of O6 carbon-based-nano LiFePO4 composite material at 0.5C;
[0022] Fig.10 The C6H prepared by the present invention 12 The charge-discharge curve of O6 carbon-based nano-LiFePO4 composite material at 1C for 200 cycles;
[0023] Fig.11 The C6H prepared by the present invention 12 The charge-discharge curve of the O6 carbon-based-nano LiFePO4 composite material returns to 0.1C after 100 cycles at 1C;
[0024] Fig.12 The C6H prepared by the present invention 12 The charge and discharge curve of O6 carbon-based-nano LiFePO4 composite material at 5C for 1050 cycles. DETAILED DESCRIPTION
[0025] Embodiment 1:
[0026] A method for preparing a carbon-based-nano LiFePO4 composite positive electrode material comprises the following steps:
[0027] Walnut shells, ginkgo leaves and bamboo powder biomass are used as raw materials and carbonized at 300℃-600℃ for 0.5h-3h in a tubular furnace under an inert atmosphere. After removing volatile substances, the biomass carbon source is obtained; then NaCl-KCl (molar ratio of 1:1) is used as the molten salt medium, Na2CO3, K2CO3 and KOH are used as pore-forming agents, and the mass ratio of pore-forming agent to reactant is 0.3-3. In a tubular furnace under an inert atmosphere, a porous carbon-based material is prepared at 800℃-1300℃. Figure 4This is the SEM morphology of the mass ratio of K2CO3 to bamboo powder of 0.6:1. It can be seen from the figure that after the addition of the pore-forming agent, the macroscopic morphology of the bamboo powder becomes porous. Studies have shown that it is feasible to use K2CO3 as an etchant, and the porous carbon base can provide more attachment points for nano-LiFePO4. Figure 5 The CH prepared in NaCl-KCl (molar ratio of 1:1) molten salt medium 12 O6 carbon-based SEM morphology, from which we can see that C6H prepared in molten salt medium 12 The O6 carbon-based material has a smooth surface and clear outlines, but can still provide attachment points for nano-LiFePO4, indicating that the preparation of carbon-based-nano-LiFePO4 composite materials is feasible.
[0028] Embodiment 2:
[0029] A method for preparing a carbon-based-nano LiFePO4 composite positive electrode material comprises the following steps:
[0030] NaCl-KCl (molar ratio of 1:1) was selected as the molten salt medium, and NH4H2PO4, FeC2O4·2H2O, CH3COOLi, C6H 12 O6 is used as raw material, porous carbon-based materials are added, the molar ratio of molten salt / reactant raw materials is prepared in the range of 0.3:1-3:1, and a multi-molecular carbon source is used as a binder. The reactant raw materials are weighed in proportion, mixed and loaded into a crucible, and placed in a tubular furnace for heating. An inert atmosphere is introduced, and when the temperature rises to 600℃-900℃, the porous carbon-based material and carbon nano-LiFePO4 are self-assembled in the molten salt. After keeping warm for 0.2h-8h, the temperature is lowered, and the furnace is cooled to room temperature, washed with hot water, filtered to separate the molten salt, and dried to prepare a powder, which is a carbon-based-nano LiFePO4 composite positive electrode material. The macroscopic morphology of the powder is as follows Figure 1 As shown in , the powder is gray-black and fine-grained.
[0031] Test example
[0032] (1) XRD test
[0033] Figure 1 Shows C6H 12 O6 and pure nano-LiFePO4 synthesized in molten salt by the same method in the 2θ range of 10°-80°. It can be seen from the figure that the single and well-crystallized pure nano-LiFePO4 obtained, and the amorphous carbon (C6H 12 O6) base mainly presents an amorphous morphology (see Figure 2 ),Depend on Figure 3 It can be seen that this study has successfully synthesized carbon-based-nano LiFePO4 composite materials.
[0034] (2) SEM test
[0035] To better understand (C6H 12 O6) base and nano-LiFePO4, and the SEM image of the material obtained after the two are self-assembled (see Figure 6 ), the study showed that the molten salt method can embed nano-LiFePO4 well into C6H 12 O6 carbon matrix, and presents bulk inlay and surface inlay respectively, while C6H 12 The O6 carbon base presents a porous carbon skeleton morphology during the self-assembly process. This is because when acetate substances exist in the molten salt, the volatile substances decompose at high temperature to make C6H 12 O6 carbon base presents a porous carbon skeleton morphology during the self-assembly process. 12 The porous carbon skeleton morphology uniformly dispersed on the O6 carbon matrix provides more sites for nano-sized LFP particles, which is beneficial to the transmission of electrons and ions. In summary, combined with the XRD and SEM data analysis, it can be seen that the preparation of carbon-based-nano LiFePO4 composite materials is feasible.
[0036] (3) Button battery test
[0037] The constant current charging method was used to test the cycle performance of the prepared button cell. The instrument used was the Blue Electric Battery Test System, the nominal specific capacity of LiFePO4 was 170mAh / g (1C = 170mA / g), the prepared battery was tested at 25°C, and the specific charge and discharge program was set as follows: standing for 10h → constant current charging to a voltage of 1.8V → 4.3V → standing for 2min → constant current discharge to a voltage of 1.8V → standing for 5min, and the cycle test was carried out at 0.1C, 0.5C, 1C, and 5C respectively according to the above program, and the cycle-specific capacity, discharge time-specific capacity, and voltage-specific capacity curves of the samples were obtained. Assembly of button cells: According to the positive electrode material (LiFePO4): polyvinylidene fluoride (PVDF): Super P mass ratio of 8:1:1, 1.6g of positive electrode material, 0.2g of polyvinylidene fluoride (PVDF), and 0.2g of Super P were put into a mortar and ground for 15 minutes, mixed evenly, and N-methylpyrrolidone (NMP) was added and ground for 5 minutes to obtain a mixed slurry. The slurry was evenly applied to the matte surface of the aluminum foil with a coating machine, dried at 120°C for 4h, and the aluminum foil was placed at 90°C for 10h to remove the residual NMP solvent. Battery assembly: In an argon atmosphere glove box, place the shrapnel, gasket, and negative electrode sheet (metal lithium sheet) in the CR2025 negative electrode shell in turn and place it in the middle, add about 20L of electrolyte (1 mol / L LiPF6 dissolved in EC: DMC: EMC = 1:1:1 mixed solvent), then place the diaphragm (polypropylene PP, Celgard2400 type) in turn, add electrolyte, and positive electrode sheet, and finally use a button battery sealing machine to press and seal.
[0038] To better describe the charge and discharge performance of carbon-based-nano LiFePO4 composite materials.
[0039] Figure 7 Under 0.1C conditions (C6H 12 O6)-based / nano-LiFePO4 charge-discharge curves for 60 cycles show that (C6H 12 The charge and discharge capacity of O6-based / nano-LiFePO4 has exceeded the theoretical capacity of LiFePO4 by 170 mAh / g, and the capacity has not shown a decreasing trend after 60 cycles.
[0040] Figure 8 Under 0.1C conditions (C6H 12 O6) based / nano-LiFePO4 dQ / dV diagram. It can be seen from the figure that all dQ / dV show a similar pair of cathode and anode peaks, corresponding to Fe 2+ / Fe 3+ The reversible redox reaction of the electroactive material indicates that nano-LiFePO4 plays the main role in the charge and discharge process.
[0041] Fig. 9 The C6H prepared by the present invention 12 The specific capacity-voltage curve of O6 carbon-based-nano LiFePO4 composite material at 0.5C. It can be seen from the figure that under 0.5C conditions (C6H 12 O6) based / nano-LiFePO4 specific capacity ≥140mAh / g;
[0042] Fig.10 The C6H prepared by the present invention 12 The charge-discharge curve of O6 carbon-based nano-LiFePO4 composite material at 1C cycle for 200 cycles shows that (C6H 12 The charge and discharge capacity of O6-based / nano-LiFePO4 is ≥131.1mAh / g, and the capacity still shows no decreasing trend after 200 cycles.
[0043] Fig.11 The C6H prepared by the present invention 12 The charge-discharge curve of the O6 carbon-based nano-LiFePO4 composite material returns to 0.1C after 100 cycles at 1C. It can be seen that under 1C conditions (C6H 12 After 100 cycles of O6)-based / nano-LiFePO4, the capacity returned to 0.1C and was still 194.6mAh / g. After 100 cycles, the capacity still showed no decreasing trend, which indicated that it had good rate performance.
[0044] Fig.12 The C6H prepared by the present invention 12 The charge-discharge curve of O6 carbon-based nano-LiFePO4 composite material at 5C cycle 1050 cycles shows that under 5C conditions (C6H 12 The capacity of O6-based / nano-LiFePO4 after 1050 cycles is still ≥43.4 mAh / g, which indicates good rate performance.
[0045] Table 1 shows the charge-discharge specific capacity and charge-discharge efficiency of the ginkgo leaf carbon-based nano-LiFePO4 and the walnut carbon-based nano-LiFePO4 in Example 2. As can be seen from the table, both the ginkgo leaf carbon-based and the walnut carbon-based nano-LiFePO4 are feasible.
[0046] Table 1 0.1C charge-discharge specific capacity and charge-discharge efficiency of ginkgo leaf carbon-based / walnut carbon-based nano-LiFePO4
[0047] project Charging capacity mAh / g Discharge capacity mAh / g efficiency(%) <![CDATA[Ginkgo leaf base / nano LiFePO4]]> 210.93 203.67 96.56 <![CDATA[Walnut-based / Nano LiFePO4]]> 215.81 201.15 93.21
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, substitution and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-based-nano LiFePO4 composite positive electrode material, characterized in that: The following steps are involved: (1) Walnut shells, ginkgo leaves, and bamboo powder biomass were used as raw materials. In a tubular furnace, under an inert atmosphere, they were carbonized at 300°C-600°C for 0.5h-3h. After removing volatile substances, the biomass carbon source was obtained. Then, NaCl-KCl (molar ratio of 1:1) was used as the molten salt medium, Na2CO3, K2CO3, and KOH were used as pore-forming agents, and the mass ratio of pore-forming agent to reactant was 0.3-3. In a tubular furnace, under an inert atmosphere, at 800°C-1300°C, porous carbon-based materials were prepared. (2) NaCl-KCl (molar ratio of 1:1) was selected as the molten salt medium, and NH4H2PO4, FeC2O4·2H2O, CH3COOLi, C6H 12 O6 is used as a raw material, and the porous carbon-based material prepared by the present invention or commercial graphene is added. The molar ratio of the molten salt / reactant raw material is prepared in the range of 0.3:1-3:1, and a multi-molecular carbon source is used as a binder. The reactant raw materials are weighed in proportion, mixed and loaded into a crucible, and placed in a tubular furnace for heating. An inert atmosphere is introduced, and when the temperature rises to 600°C-900°C, self-assembly of the porous carbon-based material and carbon nano-LiFePO4 is achieved in the molten salt. The temperature is maintained for a range of 0.2h-8h and then reduced, and the powder is cooled to room temperature with the furnace, washed with hot water, filtered to separate the molten salt, and dried to prepare a powder, which is a carbon-based-nano LiFePO4 composite positive electrode material.
